2022
DOI: 10.1186/s13054-022-04161-3
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial effects of angiotensin II compared to norepinephrine in an animal model of septic shock

Abstract: Background Angiotensin II is one of the vasopressors available for use in septic shock. However, its effects on the septic myocardium remain unclear. The aim of the study was to compare the effects of angiotensin II and norepinephrine on cardiac function and myocardial oxygen consumption, inflammation and injury in experimental septic shock. Methods This randomized, open-label, controlled study was performed in 20 anesthetized and mechanically ventilated pigs. Septic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…1 and Table 1 ). However, due to species differences with humans, normal lactate levels are usually observed in swine septic shock 35 despite developing all the criteria for a septic shock and tissular hypoperfusion 36 . According to the surviving sepsis campaign guidelines from 2013 25 , which were the only available at the time this protocol was designed, severe sepsis was defined as sepsis plus sepsis-induced organ dysfunction or tissue hypoperfusion; our porcine sepsis phenotype is therefore compatible with this definition.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Table 1 ). However, due to species differences with humans, normal lactate levels are usually observed in swine septic shock 35 despite developing all the criteria for a septic shock and tissular hypoperfusion 36 . According to the surviving sepsis campaign guidelines from 2013 25 , which were the only available at the time this protocol was designed, severe sepsis was defined as sepsis plus sepsis-induced organ dysfunction or tissue hypoperfusion; our porcine sepsis phenotype is therefore compatible with this definition.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical parameters measured at the timepoint just before euthanizing are summarized in Table 1 . A more comprehensive description of the model severity and the response to resuscitation care can be found in the princeps study publication [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The collaborative study reported here is an example. Liver biopsies and plasma were isolated from septic shock pigs that were also used in a study on the myocardial effects of vasopressors [ 17 ]. Due to logistical reasons, we were, however, not able to quantify FFA β-oxidation ex vivo in the pig samples, so conclusive proof of the link between PPARα resistance on the one hand and FFA increase and lipotoxicity on the other is lacking in pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the progressive loss of ACE2 in COVID-19 shifts the system to an overall higher angiotensin level due to the impaired ability of ACE2 to degrade it, which may explain the hemodynamic stability during the initial stages of the disease [ 64 ]. Moreover, recent experimental evidence suggests that angiotensin-II administration is associated with a similar level of cardiovascular resuscitation, less myocardial oxygen consumption, and less inflammation compared to norepinephrine [ 65 ]. Taking into consideration the characteristics of angiotensin-II, more research is needed to evaluate its potent effects in COVID-19-related shock.…”
Section: Discussionmentioning
confidence: 99%